PENGARUH ATRIBUT SUPERMARKET TERHADAP IMPULSE BUYING (SURVEI PADA SUPERMARKET DI KOTA BANDUNG) - Arifianti, Ria (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2010)
This research is conducted to analyze the influence of attribute supermarket  on impulse buying  at Supermarket Bandung. The Goal of this research is also to know the attribute supermarket that influence the impulse buying , supporting factors and how the problems take place.The descriptive-verificative method is used in this research. Data collection methods are literature and field studies. Field study covers observation, interview and structural questionnaires. The questionnaires are given to 75  consumers at Supermarket Bandung. The sistematic sampling is used as sampling tecgnique. Data are analyzed by qualitative analysis and correlation multiple regresion statistical.The analysis confirms that there are influences on attribute supermarket , impulse buying at Supermarket  Bandung.  That is, if  attribute supermarket is carefully done, it will increase the impulse buying.